PERCEPTIONS TOWARDS TEENAGE PREGNANCY AND LIFESTYLES DETERMINANTS AMONG PREGNANT ADOLESCENTS - Lyidia Dahlia Dahlan; Dorothy Anak Kulai, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Teenage pregnancy is still a social problem with physical and psychological implications in many countries worldwide. This study aimed to examine the perceptions of teenage mothers toward pregnancy and their lifestyle determinants. A cross-sectional study was carried out among a convenience sample of 30 teenage mothers who attended one purposefully selected Maternal Child Health Clinic in Kuching. The study involved 30 teenage mothers between 13 and 19 years of age who had registered with an antenatal clinic and attended the follow-up. The perceptions of teenage mothers towards pregnancy were more often negative, with 19 (63.3%) having no knowledge of prevention and 11 (36.7%) having some knowledge of pregnancy prevention. Lifestyle determinants of teenage mothers included parents who were concerned about social limitations; loitering or socializing with friends and consuming alcohol can increase the desire for sex, clubbing, and smoking. Findings from this study have shown that 87% of teenage mothers enjoyed loitering or socializing with friends, with clubbing as their main activity. It was found that 66.7% were smokers and 73% consumed alcohol. In addition, 80% of the teenage mothers claimed they were having less communication with their parents despite staying with them. In conclusion, the perceptions and lifestyles adopted by teenagers were significantly related to being pregnant at a young age.